Quadriceps strength, inter‐extremity difference (IED) and joint status in adult persons with severe haemophilia in different age stages. (11th October 2012) - Brunner, A.; Stäuber, F.; Göhler, S.; Czepa, D.; Krüger, S.; Wendel, M.; Seuser, A.; Hilberg, T.
Summary Quadriceps weakness seems to be a hallmark in adult persons with severe haemophilia (PWH). The purpose of this study was to compare PWH and non‐haemophilic controls in different age stages with reference to joint status and quadriceps strength. Further aims were to examine the extent of strength‐specific inter‐extremity‐difference (IED) and the prevalence of abnormal IED (AIED). A total of 106 adults with severe haemophilia (H) and 80 controls (C) had undergone an orthopaedic examination for classification of knee and ankle status using the WFH score. Quadriceps strength was evaluated unilaterally as well as bilaterally with a knee extensor device. Each group was divided into four age‐related subgroups (HA/CA: 18–29, HB/CB: 30–39, HC/CC: 40–49, HD/CD: 50–70; in years). H presented a worse knee and ankle status than C indicated by higher WFH scores (P < 0.01). Regarding the age‐matched subgroups only HB showed higher knee scores than CB (P < 0.05). The ankles were clinically more affected in HB‐HD compared with those in age‐matched controls (P < 0.05). H showed lower quadriceps strength than C (P < 0.05). In addition, all subgroups of H presented lower strength (HA: 10–17, HB: 19–23, HC: 35–36, HD: 53–61; in%, P < 0.05). IED was higher in H than in C [H: 12.0 (5.3/32.2) vs. C: 7.1 (2.9/10.9); Median (quartiles) in%, P < 0.001] and increased with age in H. We discovered an AIED in 35% of H. These findings highlight the importance for the early implementation of preventive and rehabilitative muscle training programmes in the comprehensive treatment of PWH.